Polo-like kinase 1 as a potential therapeutic target and prognostic factor for various human malignancies: A systematic review and meta-analysis - Wang, Ming-Wen; Li, Zhong; Chen, Li-Hong; Wang, Ning; Hu, Jian-Ming; Du, Jin; Pang, Li-Juan; Qi, Yan (Frontiers in Oncology, 2022)
Objective The overexpression of polo-like kinase 1 (PLK-1) has been found in a broad spectrum of human tumors, making it an attractive prognostic tumor biomarker. Nowadays, PLK-1 is considered a cancer therapeutic target with clinical therapeutic value. The aim of the present study was to systematically review the prognostic and therapeutic value of PLK-1 in different malignant neoplasms. Methods A systematic literature search of the Cochrane Library, PubMed, Web of Science, and China National Knowledge Internet (CNKI) databases was conducted between December 2018 and September 2022. In total, 41 published studies were screened, comprising 5,301 patients. We calculated the pooled odds ratios (ORs) and corresponding 95%CIs for the clinical parameters of patients included in these studies, as well as the pooled hazard ratios (HRs) and corresponding 95% CIs for 5-year overall survival (OS). Results Our analysis included 41 eligible studies, representing a total of 5,301 patients. The results showed that overexpression of PLK-1 was significantly associated with poor OS (HR, 1.57; 95% CI, 1.18–2.08) and inferior 5-year disease-free survival/relapse-free survival ((HR, 1.89; 95% CI, 1.47–2.44). The pooled analysis showed that PLK-1 overexpression was significantly associated with lymph node metastasis, histological grade, clinical stages (p < 0.001 respectively), and tumor grade (p < 0.001). In digestive system neoplasms, PLK-1 overexpression was significantly associated with histopathological classification, primary tumor grade, histological grade, and clinical stages (p = 0.002, p = 0.001, p < 0.0001, respectively). In breast cancer, PLK-1 was significantly associated with 5-year overall survival, histological grade, and lymph node metastasis (p < 0.001, p = 0.003, p < 0.001, respectively). In the female reproductive system, PLK-1 was significantly associated with clinical stage (p = 0.011). In the respiratory system, PLK-1 was significantly associated with clinical stage (p = 0.021). Conclusion Our analysis indicates that high PLK-1 expression is associated with aggressiveness and poor prognosis in malignant neoplasms. Therefore, PLK-1 may be a clinically valuable target for cancer treatment.